2019
DOI: 10.1111/1750-3841.14987
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ι‐ and κ‐carrageenan addition on freezing process and ice crystals structure of strawberry sorbet frozen by various methods

Abstract: The aim of this work was to study the influence of ι‐ and κ‐carrageenan addition to strawberry sorbet prepared by various freezing methods (cryostat and conventional freezer) on freezing kinetics and ice crystals structure. Four variants of strawberry‐based sorbet were prepared: with no additive, with 0.1% addition of ι‐ and κ‐carrageenan, and 1:1 blend of both. Freezing curves and freezing time, as well as the size and morphology of ice crystals, were analyzed. The addition of carrageenan stabilizers resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…but at the same time it could be very effective in water ice cream structure protection combined with the kappa form(Kamińska- Dwórznicka et al, 2020) Kiran-Yildirim et al (2021a). also claimed that kappa carrageenan has higher activity than iota and lambda fractions, and these two fractions were included in the commercial carrageenan used for this research.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…but at the same time it could be very effective in water ice cream structure protection combined with the kappa form(Kamińska- Dwórznicka et al, 2020) Kiran-Yildirim et al (2021a). also claimed that kappa carrageenan has higher activity than iota and lambda fractions, and these two fractions were included in the commercial carrageenan used for this research.…”
mentioning
confidence: 81%
“…By preventing excessive growth of ice crystals, they improve the organoleptic properties of the product (Kamińska-Dwórznicka, Matusiak, et al, 2015). Kamińska-Dwórznicka et al (2020) reported that iota form (usually used in milk products) demonstrated ice recrystallization inhibition (IRI) activity also in sorbets, composed mainly of fruit pulp, water, and sweeteners.…”
mentioning
confidence: 99%
“…In conditions of high content of free water, the crystallization process becomes too pronounced and the size of ice crystals in ice cream often reaches 100 μm [ 13 ]. In the presence of large ice crystals, this product acquires a coarse crystalline structure, a snowy or icy consistency, which is negatively perceived by consumers [ 15 , 16 , 17 ]. The speed and degree of the recrystallization process also depend on the functional and technological properties of structure stabilizers [ 18 ], which bind free water, increase the viscosity of ice cream mixtures and, accordingly, reduce the size of air bubbles and stabilize them.…”
Section: Introductionmentioning
confidence: 99%
“…ι-carrageenan has been widely used in the food, medical, and material industries because of its gelling properties, stability, and synergistic effects. For example, the good stability of ι-carrageenan makes the addition of ι-carrageenan to ice cream reduce the growth of ice crystals [ 5 ]. The gelling properties of ι-carrageenan and the low toxicity of the digestive products allow the preparation of novel ι-carrageenan/gelatin hydrogel capsules [ 6 ].…”
Section: Introductionmentioning
confidence: 99%